EVALUATION OF THE EFFECTIVENESS AND EFFICIENCY OF MARKETING CHANNELS IN AGRICULTURAL PRODUCT DISTRIBUTION: A LITERATURE REVIEW OF STRUCTURE, FUNCTION, AND IMPACT ON FARMER INCOME - Hadenan Towpek; Ellyta Ellyta (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study aims to evaluate the effectiveness and efficiency of marketing channels in the distribution of agricultural products and to analyse the influence of channel structure and function on farmers' income. This study uses a literature review method with a descriptive qualitative approach through an examination of various scientific literature, previous research results, and agricultural economic policy publications. The results of the study show that the effectiveness of marketing channels is determined by the ability of the distribution system to distribute products quickly, accurately, and with minimal cost, while efficiency is related to the optimisation of resources to achieve maximum results. Long and inefficient channel structures generally cause a decline in profit margins at the farmer level because most of the added value is absorbed by intermediaries. Conversely, simple, integrated channel structures and functions supported by supporting functions such as price information, logistics, and cooperative institutions can significantly increase farmers' income. This study also emphasises the importance of modernising marketing systems through digitalisation, strengthening farmer institutions, and supporting public policies that favour producer welfare. Optimising the effectiveness and efficiency of agricultural marketing channels is key to improving the competitiveness and economic stability of farmers in the era of globalisation.